2008
DOI: 10.1016/j.virol.2008.07.039
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine mediated molecular tuning of astrocytes for enhanced permissiveness to HIV infection

Abstract: We report in this study that minimum productive HIV infection in astrocytes (a predominant cell type in brain and persists for the entire life) occurs through endocytosis. The lysosomotropic agent chloroquine enhanced permissiveness of astrocytes to HIV infection possibly by circumventing degradation of endosome-entrapped viral particles. In particular, chloroquine may promote establishment of a stable long term viral reservoir in astrocytes and may eventually facilitate early onset of neurological complicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
107
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(118 citation statements)
references
References 14 publications
11
107
0
Order By: Relevance
“…HIV enters astrocytes in a nonclassical way, either via endocytosis and escape of HIV from the endosome (27,30,42), utilization of alternative receptors for HIV entry including the promiscuous CC chemokine receptor D6 (28), or a decreased requirement of neurotropic HIV strains for CD4 (16). Despite lack of a clear understanding of how HIV enters astrocytes, a number of groups of investigators have demonstrated the presence of HIV protein and/or DNA within astrocytes in HIV-positive (HIV ϩ ) postmortem tissue (11,15,29,40,41,44).…”
Section: Discussionmentioning
confidence: 99%
“…HIV enters astrocytes in a nonclassical way, either via endocytosis and escape of HIV from the endosome (27,30,42), utilization of alternative receptors for HIV entry including the promiscuous CC chemokine receptor D6 (28), or a decreased requirement of neurotropic HIV strains for CD4 (16). Despite lack of a clear understanding of how HIV enters astrocytes, a number of groups of investigators have demonstrated the presence of HIV protein and/or DNA within astrocytes in HIV-positive (HIV ϩ ) postmortem tissue (11,15,29,40,41,44).…”
Section: Discussionmentioning
confidence: 99%
“…Conceivably, blockade of TLR7/TLR8 signaling may limit induction of host antiviral defenses such as those mediated by type 1 interferons. Alternatively, the effect on plasma viremia could have been the result of a direct enhancement of infectivity by chloroquine, a finding in some in vitro studies, 38,39 while others have shown chloroquine to inhibit HIV replication. 40,41 Other researchers have assessed the effects of chloroquine or hydroxychloroquine, a related compound, on immune activation in HIV-infected participants.…”
Section: Figmentioning
confidence: 99%
“…Briefly, 17 μg of each of the respective HIV-1 DNA vectors was transfected in 100 mm culture dishes (BD Falcon) using Lipofectamine 2000 (Invitrogen) as described earlier (Vijaykumar et al, 2008;Chauhan et al, 2014). Similarly, HIV-1 NLENY1 was pseudotyped with VSV-G envelope using 4.0 μg of VSV-G expression vector.…”
Section: Virus Packaging and Pseudotypingmentioning
confidence: 99%
“…Primary cultures (HFA and HFN) were characterized using immunofluorescence staining as described previously (Vijaykumar et al, 2008;Mehla et al, 2012). Slide flaskets (Nunc) were coated with poly-D-lysine; on the next day primary neurons were seeded.…”
Section: Immunofluorescence and Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation